The Role of BUMDes in Preserving the Environment in Pematang Lingkung Village, Batang Merangin District, Kerinci Regency, Jambi Province - Arneli Puspita; Zulkifli Alamsyah; Zamzami Zamzami (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Environmental conservation determines the life of humans and other living things, but on the other hand, humans can also select the state of their environment. With the lack of public knowledge about preserving the environment, people unwittingly pollute the environment by littering on empty land that is not used. There is a buildup of waste that pollutes the air, water, and soil. The Pematang Lingkung Village Government takes steps through the BUMDes Program to prevent environmental pollution by utilizing vacant land that is not used as a tourist spot in the form of the Melik Sisik Park as an effort to preserve the environment. This study aimed to determine the condition of BUMDes and the role of BUMDes in environmental conservation. This type of research uses a quantitative approach with 80 respondents. Sampling technique with a questionnaire instrument was employed. Descriptive data analysis and Chi-Square test was conducted to analyze the results. A qualitative approach is used to understand the development and dynamics of BUMDes in the context of rural economic development, especially in rural community business processes. The industry's environmental management and monitoring implementation had not raised awareness of environmental conservation; community involvement and concern in ecological management and monitoring are still low. The results showed a relationship between the role of BUMDes and environmental conservation in Pematang Lingkung Village.